2012
DOI: 10.1136/annrheumdis-2012-202231
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of strontium ranelate in the treatment of knee osteoarthritis: results of a double-blind, randomised placebo-controlled trial

Abstract: BackgroundStrontium ranelate is currently used for osteoporosis. The international, double-blind, randomised, placebo-controlled Strontium ranelate Efficacy in Knee OsteoarthrItis triAl evaluated its effect on radiological progression of knee osteoarthritis.MethodsPatients with knee osteoarthritis (Kellgren and Lawrence grade 2 or 3, and joint space width (JSW) 2.5–5 mm) were randomly allocated to strontium ranelate 1 g/day (n=558), 2 g/day (n=566) or placebo (n=559). The primary endpoint was radiographical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
156
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(169 citation statements)
references
References 37 publications
1
156
2
6
Order By: Relevance
“…80 Following these negative studies, there has been a recent resurgence of interest in manipulating bone turnover for the treatment of OA following the publication of the SEKOIA trial of strontium ranelate for the treatment of knee OA. 81 This mixedgender, multicentre study demonstrated a reduction in the progression of JSN in the treatment group over a 3-year period, 81 and as such it has been heralded as the first positive Osteoarthritis and bone mineral density SA Hardcastle et al disease-modifying OA drug trial. However, in contrast to the radiographic findings, a small beneficial effect on symptoms in this trial was confined to the group taking the higher (2 g per day) dose.…”
Section: Mechanisms Including Recent Insights From Genetic Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…80 Following these negative studies, there has been a recent resurgence of interest in manipulating bone turnover for the treatment of OA following the publication of the SEKOIA trial of strontium ranelate for the treatment of knee OA. 81 This mixedgender, multicentre study demonstrated a reduction in the progression of JSN in the treatment group over a 3-year period, 81 and as such it has been heralded as the first positive Osteoarthritis and bone mineral density SA Hardcastle et al disease-modifying OA drug trial. However, in contrast to the radiographic findings, a small beneficial effect on symptoms in this trial was confined to the group taking the higher (2 g per day) dose.…”
Section: Mechanisms Including Recent Insights From Genetic Studiesmentioning
confidence: 97%
“…However, in contrast to the radiographic findings, a small beneficial effect on symptoms in this trial was confined to the group taking the higher (2 g per day) dose. 81 As discussed by Lafeber and van Laar 82 in their accompanying editorial, a number of questions remain to be addressed before strontium can be adopted clinically as a treatment for OA, and recent concerns regarding the cardiovascular safety of this drug may prove prohibitive in the patient group most in need; 83 nevertheless, these results lend further support to the concept of using pharmacotherapies targeting bone to treat OA.…”
Section: Mechanisms Including Recent Insights From Genetic Studiesmentioning
confidence: 99%
“…In 2 studies by Reginster et al [39,40] comparing strontium ranelate with placebo in patients with OA, strontium ranelate seemed to have positive effects, with less degradation of joint space width in the knee, especially with a dosage of 2 g daily. Despite these positive results, however, studies with longer follow-up are needed to determine the drug's safety with longterm use.…”
Section: Strontium Ranelatementioning
confidence: 98%
“…50,51 However, in light of emerging data on cardiovascular risks, the potential benefits may not be justifiable. 52 Commercial stem cell therapies have recently emerged for knee osteoarthritis.…”
Section: David Hunter Is An Author On the Osteoarthritis Research Socmentioning
confidence: 99%